2014
DOI: 10.1364/ol.39.006217
|View full text |Cite
|
Sign up to set email alerts
|

Automatic laser welding and milling with in situ inline coherent imaging

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX; posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXX Though new affordable high power laser technologies make possible many processing applications in science and industry, depth control remains a serious technical challenge. Here we show that inline coherent imaging, with line rates up to 312 kHz and microsecond-duration capture times, is capable of directly measuring laser penetration depth in a process as violent as kWclass keyh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…A Nikon DS-Fi2 camera attached to a Nikon Epiphot microscope and Nikon NIS Elements software captured micrographs of the welds. Detailed descriptions of ICI are available in the literature, [18][19][20] so only a brief discussion of the important features is given here. ICI utilises a Michelson interferometer construction with a reference and probe beam, using a superluminescent diode with a wavelength of 843 nm and FWHM of 20 nm as the light source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Nikon DS-Fi2 camera attached to a Nikon Epiphot microscope and Nikon NIS Elements software captured micrographs of the welds. Detailed descriptions of ICI are available in the literature, [18][19][20] so only a brief discussion of the important features is given here. ICI utilises a Michelson interferometer construction with a reference and probe beam, using a superluminescent diode with a wavelength of 843 nm and FWHM of 20 nm as the light source.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ICI has been used to measure the drill hole depth in ferrous alloys during laser machining, 18,19 and its application in laser welding is just beginning. 20 In this paper, the utility of ICI to provide real time measurements of keyhole depth is demonstrated in DH36 steel, 304 stainless steel, InconelH Alloy 690, Ti-6Al-4V, and 2219 aluminium alloys. A wide range of industries, including construction, energy, aerospace, and automotive, utilise and join the alloys used in this study or compositionally similar alloys.…”
Section: Introductionmentioning
confidence: 99%
“…A 50:50 fiber coupler connects the four sections of the system as illustrated in Figure (adapted from ref. ). The imaging light source is a superluminescent diode (SLD) with a center wavelength of 840 nm and spectral bandwidth of 25 nm (Superlum BLM‐S‐840‐G‐I‐30).…”
Section: Methodsmentioning
confidence: 97%
“…Work by Blecher et al (2014) demonstrated the ability of ICI to measure laser keyhole depths in a range of metals, including DH36 steel, 304 stainless steel, Inconel 690, Ti-6Al-4V, and 2219 aluminum alloy. Webster et al (2014) exploited the utility of ICI for feedback control in high-power laser welding applications. Ji et al (2015) demonstrated ICI deployment through a high-speed galvanometer scanner.…”
Section: Introductionmentioning
confidence: 99%